2018
DOI: 10.1007/s00425-018-2985-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of an oxidosqualene cyclase (PdFRS) encoding a monofunctional friedelin synthase in Populus davidiana

Abstract: An oxidosqualene cyclase (PdFRS) from Populus davidiana was characterized as a monofunctional friedelin synthase by its heterologous expression in yeast and overexpression in plants. Triterpenes are one of the largest classes of plant chemical compounds composed of three terpene units, which form the basic skeleton of all sterols and saponins. Friedelin (friedelan-3-one), a pentacyclic triterpene, occurs in many plant families and is particularly present in rich amounts in cork tissues from trees. The biosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…By contrast, Tw OSC1 and Tw OSC3 clustered with Mi FRSs and Pd FRS into a clade. As previously described (Souzamoreira et al ., ; Han et al ., ), both Mi FRSs and Pd FRS were monofunctional friedelin synthases, that can produce friedelin only. Interestingly, there was also a multiproduct friedelin synthase, Kd FRS (Wang et al ., ), which could produce friedelin as a major product, taraxerol, and β‐amyrin as a minor product.…”
Section: Resultsmentioning
confidence: 95%
“…By contrast, Tw OSC1 and Tw OSC3 clustered with Mi FRSs and Pd FRS into a clade. As previously described (Souzamoreira et al ., ; Han et al ., ), both Mi FRSs and Pd FRS were monofunctional friedelin synthases, that can produce friedelin only. Interestingly, there was also a multiproduct friedelin synthase, Kd FRS (Wang et al ., ), which could produce friedelin as a major product, taraxerol, and β‐amyrin as a minor product.…”
Section: Resultsmentioning
confidence: 95%
“…4C), including residues in positions 749 and 426 (associated with lupeol synthesis), 742 (associated with multifunctional amyrin synthase activity), and 496 of our alignment (associated with friedelin synthesis). Previous sequence comparisons 37 and point mutation studies 38,39 demonstrated the residue in the latter position (Leu-491 in QsOSC3, position 496 in the alignment) as critical for friedelin synthesis. These results, combined with ours, underscore the power of association analyses to identify residues associated with specific catalytic activity and the extensive impact single amino acid substitutions can have on the catalytic activity of specialized metabolic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…After SE overexpression, the content of ganoderic acid in Ganoderma lingzhi was 2 times higher than that of the wild type (Zhang et al 2017a). In Populus davidiana, overexpression of OSC increased friedelin accumulation by 233-445% compared with the non-transgenic plants (Han et al 2019). However, the effects of overexpression of TwSQS, TwSE and TwOSC on celastrol biosynthesis in T. wilfordii CMCs and DDCs still remain unknown.…”
Section: Introductionmentioning
confidence: 99%